1996
DOI: 10.1099/13500872-142-5-1231
|View full text |Cite
|
Sign up to set email alerts
|

In vitro phagocytosis and survival of Streptococcus suis capsular type 2 inside murine macrophages

Abstract: Opsonized or non-opsonized bacteria were incubated with macrophages in vitro and samples were obtained after 1 and 3 h incubation. Phagocytosis as well as live and dead intracellular organisms were determined by acridine orange and crystal violet staining. After 1 h incubation, non-opsonized virulent and non-virulent capsulated bacteria were poorly phagocytosed (by less than 7 O/ O of the macrophages), whereas the non-capsulated non-virulent mutant strain was highly phagocytosed (by more than 68% of the macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 35 publications
4
27
0
Order By: Relevance
“…The growth rates of strains tested in bacterial culture media were similar and thus not pertinent to the observed differences in bacterial survival. For several streptococcal pathogens, extracellular polysaccharide capsule (GAS, GBS, Streptococcus pneumoniae, and S. suis) (4,17,24,37) and surface-associated proteins (GAS and type 3 pneumococci) (1, 12) deter phagocytosis and prevent opsonization of bacteria by complement. We have noted that disease-associated strains of S. iniae display a high buoyancy (turbid) in broth culture, whereas commensal strains have a low buoyancy, forming a granular precipitate (unpublished data) as described for the type strain (ATCC 29178) (27).…”
Section: Discussionmentioning
confidence: 99%
“…The growth rates of strains tested in bacterial culture media were similar and thus not pertinent to the observed differences in bacterial survival. For several streptococcal pathogens, extracellular polysaccharide capsule (GAS, GBS, Streptococcus pneumoniae, and S. suis) (4,17,24,37) and surface-associated proteins (GAS and type 3 pneumococci) (1, 12) deter phagocytosis and prevent opsonization of bacteria by complement. We have noted that disease-associated strains of S. iniae display a high buoyancy (turbid) in broth culture, whereas commensal strains have a low buoyancy, forming a granular precipitate (unpublished data) as described for the type strain (ATCC 29178) (27).…”
Section: Discussionmentioning
confidence: 99%
“…Our work shows that the ⌬covR mutant survived more than the wild type in human PMNs and MONOs. It is reasonable to explain this phenomenon by the thicker capsule of the ⌬covR strain, since it has been reported that the capsular polysaccharide (CPS) of S. suis protects against phagocytosis and against the bactericidal activity of leukocytes (6,9,48,59,62,63,79). The work of Segura et al demonstrated that S. suis serotype 2 is able to interact with MONOs of human origin, inducing the release of large amounts of the proinflammatory cytokines (61).…”
Section: Discussionmentioning
confidence: 99%
“…Host protection against infection caused by S. suis is known to be mediated primarily by opsonophagocytosis/killing (27,(51)(52)(53). Whereas published studies have evidenced the essential contribution of specific humoral immunity to the fight against S. suis (22)(23)(24)(25)(26)(27)54), no study has focused on the precise characteristics of protein-and CPS-specific responses after an infection with live S. suis ) or IgM antiprotein or anti-CPS titers were determined by ELISA on days 7 (n ϭ 9), 14 (n ϭ 7), and 21 (n ϭ 7) in surviving mice.…”
Section: Discussionmentioning
confidence: 99%